DETERMINAN KEJADIAN KEKURANGAN ENERGI KRONIK (KEK) PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS PEUKAN BADA KABUPATEN ACEH BESAR 2023 - Elmayanda, Elmayanda; Dewi, Rika; Saudah, Saudah; Kurniawati, Putri; Jannah, Miftahul; Arfina, Arfina (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2023)
SEZ is a condition caused by an imbalance in nutrient intake between energy and protein, so that the nutrients needed by the body are not fulfilled. The proportion of women of childbearing age at risk of SEZ in Aceh Province aged 15-19 years who were pregnant was 38.5% and those who were not pregnant was 46.6%. The purpose of the study was to determine the Determinants of Chronic Energy Deficiency (SEZ) in Pregnant Women in the Peukan Bada Health Center Working Area, Aceh Besar Regency. This research method is analytic with a Cross Sectional approach with total sampling technique with a sample size of 71 pregnant women. This research was conducted on August 4-21, 2023 with univariate and bivariate analysis with the Chi square test. The results showed that there was a relationship between occupation (0.003), knowledge (0.002), attitude (0.002), education (0.004), husband support (0.007), age (0.002), parity (0.002) and anemia (0.001) with SEZ in pregnant women. Conclusions and suggestions there is a relationship between work, knowledge, attitude, education, husband's support, age, parity and anemia with SEZ in pregnant women. It is expected for the research site to hold health counseling about SEZ and the provision of additional food additives (PMT).